Tingkat Kepuasan Pengguna Terhadap Kinerja Pelayanan Kereta Api Tanjung Karang – Kotabumi - Millennia, Alen Aquariesta; Ningsih, Panti Wahyu; Misdalena, Felly (Jurnal Talenta Sipil, 2025)
Railways as one of the means of land transportation that have an important role in population mobility. The Railway industry is an interesting sector to observe because most people use rail transportation for various destinations. One of the train stations in Bandar Lampung is Tanjung Karang Station (TNK). TNK Station is a type A large class train station located in Gunung Sari Village, Enggal District, Bandar Lampung City. Every day Tanjung Karang Railway Station has the main function as a place for passengers to get on and off. One of the Tanjung Karang Station trains that serves the Tanjung Karang-Kotabumi route is the Rajabasa Train. This study will analyze the factors of user satisfaction level on the service performance of the Rajabasa Tanjung Karang-Kotabumi Train. The specification of this study is a qualitative Descriptive Analysis research. The research is focused on customer satisfaction with the services provided on the Tanjung Karang-Kotabumi Railway Regional Division IV Tanjung Karang with the help of IBM SPSS STATISITICS software and then analyzed by testing the Validity Test, Reality Test and Customer Satisfaction Index (CSI). The results of the Customer Satisfaction Index (CSI) analysis are 63.57%, then based on the Customer Satisfaction Index (CSI) Criteria table, an index value of 51.00-65.99% is obtained with quite satisfactory information. Based on these results, the level of consumer satisfaction with the Rajabasa Train for the overall service is quite satisfactory.